Theology and rhetoric: redefining the relationship between res and verba - P. Lampe (Acta Theologica)
After discussing three models defining the relationship between rhetoric (linguistic form, verba) and theology (content, res) in scholarship’s history (part I), a theoretical discussion attempts to further undergird the third model according to which verba produce res (part II). As a first step, the inseparable intertwinement of res and verba is shown by empirical studies. The linguistic form always carries unspoken semantic content. Altering this form changes the content, even if a phrase’s logical meaning remains the same. As a farther-reaching second step, constructivist philosophy of language is used, holding that language creates reality. “Reality” is defined as constructed by the brain and language and differentiated from ontic reality. Four sources of evidence are identified that make such reality constructs plausible to groups. Part III discusses the theological concept of “new creation” in light of the second part’s findings. Part IV shows a way to overcome postmodern indifference with regard to “truth.”